1990
DOI: 10.1159/000125351
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Testicular Function in Rats

Abstract: A gonadotropin-releasing hormone (GnRH) antagonist, when injected 24 h before sacrifice to rat fetuses, did not modify plasma testosterone concentrations in males on day 18 of gestation but it did on days 19, 20 and 21. This GnRH antagonist reduced plasma luteinizing hormone (LH) levels and increased pituitary LH content in both male and female 19-day-old fetuses from mothers adrenalectomized on day 14 of gestation. An inverse relationship between plasma testosterone and LH levels was noted in males and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Early studies showed that maternal exposure to psychological stress or exogenous GCs during the last trimester decreased fetal androgen action, as evidence by decreased anogenital distance and lowered testes weight at birth as well as “feminized” sexual behavior during adulthood in male offspring [ 184-186 ]. Subsequent studies suggested that these phenotypes were established during fetal development since prenatal treatments with pharmacological GCs (DEX, betamethasone, or prednisone) as well as chronic stress during late gestation blunted gestational T in mice and rats [ 187-190 ]. Critically, the 2 studies that longitudinally measured fetal T during pregnancy showed that stress increased fetal T at gestational day 17 and decreased T during gestational days 18 to 19, when fetal T typically peaks [ 188 , 189 ].…”
Section: Evidence For Developmental Sex-steroid Disruption By Abermentioning
confidence: 99%
“…Early studies showed that maternal exposure to psychological stress or exogenous GCs during the last trimester decreased fetal androgen action, as evidence by decreased anogenital distance and lowered testes weight at birth as well as “feminized” sexual behavior during adulthood in male offspring [ 184-186 ]. Subsequent studies suggested that these phenotypes were established during fetal development since prenatal treatments with pharmacological GCs (DEX, betamethasone, or prednisone) as well as chronic stress during late gestation blunted gestational T in mice and rats [ 187-190 ]. Critically, the 2 studies that longitudinally measured fetal T during pregnancy showed that stress increased fetal T at gestational day 17 and decreased T during gestational days 18 to 19, when fetal T typically peaks [ 188 , 189 ].…”
Section: Evidence For Developmental Sex-steroid Disruption By Abermentioning
confidence: 99%
“…The process of masculinization depends on testosterone, which, by the action of the cytochrome P450 aromatase enzyme, is metabolized to estrogen in the central nervous system (CNS) (Erskine et al, 1988;Rhoda et al, 1984). In male rats, two testosterone peaks of testicular origin occur, the first at gestational days (GD) 18-19 (Weisz & Ward, 1980) and the second during the first hours after birth, lasting until postnatal day (PND) 10 (Corbier et al, 1992;Lalau et al, 1990;Wallen & Baum, 2002).…”
mentioning
confidence: 99%